Socio-economic inequalities in children's snack consumption and sugar-sweetened beverage consumption: the contribution of home environmental factors. Issue 3 (14th August 2014) - van Ansem, Wilke J. C.; van Lenthe, Frank J.; Schrijvers, Carola T. M.; Rodenburg, Gerda; van de Mheen, Dike
<x content-type="archive" xml:space="preserve">Abstract</x> In the present study, we examined the association between maternal education and unhealthy eating behaviour (the consumption of snack and sugar-sweetened beverages (SSB)) and explored environmental factors that might mediate this association in 11-year-old children. These environmental factors include home availability of snacks and SSB, parental rules about snack and SSB consumption, parental intake of snacks and SSB, peer sensitivity and children's snack-purchasing behaviour. Data were obtained from the fourth wave of the INPACT (IVO Nutrition and Physical Activity Child cohorT) study (2011), in which 1318 parent–child dyads completed a questionnaire. Data were analysed using multivariate regression models. Children of mothers with an intermediate educational level were found to consume more snacks than those of mothers with a high educational level (B= 1·22, P= 0·02). This association was not mediated by environmental factors. Children of mothers with a low educational level were found to consume more SSB than those of mothers with a high educational level (B= 0·63, P< 0·01). The association between maternal educational level and children's SSB consumption was found to be mediated by parental intake of snacks and SSB and home availability of SSB. The home environment seems to be a promising setting for interventions on reducing socio-economic inequalities in children's SSB consumption.